Problems of legal regulation for state language policy in Ukraine - Kalushka, Vira (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
A modern state acquires independence and sovereignty only when it can fully protect and secure itself and its own symbols. It is applied not only at the national and international levels, but also in individual spheres of functioning, in individual regions throughout its territory. When we talk about Ukraine as a sovereign state, we mean a free country that performs its own functions on its territory independently and as an independent subject of international relations. In this case, one of the most important elements of such a state is necessarily the Ukrainian language in the status of the only official state language.It is worth noting that the state language is one of the most important attributes of any state, it is the foundation of national identity and the basis for the formation of self-awareness and self-identification of an individual, as a citizen and representative of the respective nation. In the process of formation and development of a modern state, its language plays a major role in uniting and strengthening society. Therefore, taking into account the importance of language in the formation and development of the state and nation, it is worth paying attention to its protection at the national level. A noticeable problem of the modern language policy of Ukraine has become its discrepancy with the real language situation in the country. The reason for this is the political situation, which contributed to excessive politicization of the language issue. Therefore, from the point of view of some people, the state language is not so much an important symbol of national identity and an integral part in the mechanism of formation of an independent legal state, as a lever for various manipulations on political issues. This state of affairs makes it difficult to properly assess the situation and settle the language issue.The aim of the article is to analyze the peculiarities of the formation and implementation of the state language policy in Ukraine, the problems and shortcomings of legal support in this area, and suggestions for its improvement.